Postictal vertebral fractures: Incidence, risk factors, and clinical outcomes. A systematic review - Salvador Manrique-Guzman; Ana Karen Perez-Vazquez; Claudia Lerma; Francisco R. Revilla-Pacheco; Tenoch Herrada-Pineda; Jorge Francisco Sanchez Santa-Ana; Maria Jose Wilches-Davalos; Iliana Margarita Esquivel-Valdes; Caroline Larocque-Guzman; Tania Ivette Sanchez-Zacarias (Brain and Spine)
Introduction: Vertebral fractures in postictal patients with no prior acute or chronic trauma history are rare but can lead to severe neurological complications if missed during the initial evaluation. Research question: What are the prevalence and risk factors associated with vertebral fractures? What are the characteristics of these fractures in terms of their location, severity, and clinical outcome? Materials and methods: A comprehensive literature search using MeSH terms was conducted. Data from previously published studies and three new cases from the authors' institution were collected. The variables included demographic information, seizure history, medical comorbidities, fracture characteristics, and treatment details. Descriptive statistics summarize the data. Inferential statistics (t-test, Mann-Whitney U test, chi-squared test, Fisher's exact test, and logistic regression) were used to identify the risk factors for vertebral fractures. Results: The review included nine studies with a total of 19 patients, and three additional unpublished cases from the authors' institution. The median patient age was 50 years, with male predominance. No significant differences were found between the groups in osteoporosis, seizure history, antiepileptic drug use, or alcohol or drug abuse. The most common sites of fracture were the midthoracic spine for compression fractures and thoracolumbar junction for burst fractures. Risk factors for fractures include greater muscle mass, lower bone mineral density, longer convulsions, and recurrent convulsions. Discussion: The mechanism of injury involved violent muscle contractions during seizures. Conclusion: This review summarizes the current knowledge and provides evidence for best practices in the management of seizure-induced vertebral fractures.